(untitled) (Research, Society and Development, 2021)
This study aims to identify how the speech therapist professional helps in the early intervention of autistic children. This is an integrative literature review, with a quantitative, qualitative and descriptive approach. Data collection took place from September to November 2021, and were collected in the following databases: Virtual Health Library (VHL), Portal Capes, PubMed, Scientific Electronic Library Online (SciELO). For the research, the following descriptors were used: Speech and Hearing Science; Child Autism; Speech Therapy. The results address an analysis of articles in vernacular language on speech therapy interventions in autism. In all, eight articles met the inclusion and exclusion criteria. With 4 articles from Scielo, 2 from CAPES and 2 from the VHL. It is concluded that early intervention in ASD is the best thing that can be done to the patient and the sooner it is started, the greater the chance of controlling the child’s social and communication development. The speech therapist professional must be able to develop communication skills in autistic children, as they contribute to the promotion of learning. Thus, the speech therapist needs to be attentive to interpret and contextualize the intervention processes so that their application is flexible and benefits the patient.